Trend analysis of mortality rates and causes of death in children under 5 years of age in Xuzhou, China from 2016 to 2020 - Xu, Zhiyuan; Liu, Haonan; Zhou, Shuaishuai; Chen, Tiancheng; Meng, Chao; Li, Shengli; Yan, Xianliang; Liu, Xiao (Frontiers in Pediatrics, 2023)
Objectives To analyze the trends in mortality and causes of death among children under 5 years of age in Xuzhou, China between 2016 and 2020, in order to protect children's health and provide a basis for formulating child survival, development, and protection strategies. Methods A population-based epidemiological study was conducted. Data were obtained from the Xuzhou Center for Disease Control Prevention. We input the data into the excel database and analyzed with SPSS20.0. Results There were 1,949 children under 5 years of age died in Xuzhou, The number of deaths from 2016 to 2020 were 573 (29.40%), 577 (29.60%), 371 (19.04%), 334 (17.14%), and 94 (4.82%) respectively, mortality in children showed a downward trend. The number of deaths was relatively high in January (195 cases, 10.01%), February (190 cases, 9.75%), and May (180 cases, 9.24%), while was relatively small in July (147 cases, 7.54%), August (139 cases, 7.13%), and September (118 cases, 6.05%). The leading causes of death (COD) in children under 5 years of age were neonatal suffocation and hypoxia (323 cases, 16.57%). Pizhou (528 cases, 27.09%) showed the highest number of deaths in children under 5 years of age in China, and the Kaifa (25 cases, 1.28%) zone showed the lowest death toll. Conclusions Our research suggested that the current strategies for reducing child mortality should prioritize the actions on neonatal deaths and conduct targeted interventions for the main cause.